REKONSTRUKSI KONSEP NAFKAH DALAM HUKUM KELUARGA ISLAM: PERSPEKTIF GENDER DAN OTONOMI PEREMPUAN - Hardianti; Nurchaliq Majid (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research examines the concept of nafkah and women's autonomy from gender and Islamic family law perspectives by investigating the dynamics of nafkah interpretation and its implications for women's independence in Muslim families. Using qualitative research methods with a literature study approach, this research analyzes the thoughts of classical and contemporary scholars, especially Murtaḍhā Muṭhahhari and Faqihuddin Abdul Kodir, and contextualizes them with the social reality of Indonesian Muslim society. The results show that traditional interpretations of nafkah tend to limit women's autonomy through the construction of economic dependency, while contemporary approaches offer a more inclusive understanding that accommodates women's financial independence. Contextualization of the nafkah concept through the principle of